Regional Regulation Intervention as Legal Literacy in Empowering Village-Owned Enterprises - Moh. Taufik; Nuridin Nuridin; Mukhidin Mukhidin (International Journal of Law and Society, 2024)
Tegal Regency regional regulation Number 2 of 2018 concerning Village-Owned Enterprises is a regional policy in the context of increasing the potential of village resources. The hope is that this regional policy can be a solution for developing village potential, which in Tegal district has a lot of village development potential. As well as increasing the potential of village business capabilities. With Village-owned Enterprises, it is hoped that the business potential in Tegal Regency, which has a large number of small and medium businesses and a high entrepreneurial culture, will certainly be the main requirement if the regional government can seize this opportunity to improve and empower the business world in Tegal Regency to the maximum. This research is a Normative Juridical Research on issues relating to the Job Creation Law and Village-Owned Enterprises policies. This research aims to determine the implementation of Tegal regent's regulation number 2 of 2018 concerning village-owned enterprises as well as solutions to obstacles in its implementation., in This research uses a qualitative data analysis method, namely normative juridical which is presented descriptively. Regent's Regulation number 2 of 2018 created a main strategy, namely Tegal Regency's commitment to improving the ranking of all indicators in investment policy in a better direction, structural improvements for all indicators, implementing ease of doing business for all communities, especially micro, small and medium enterprises through village-owned enterprises.